DISSEMINATION OF RELIGIOUS MODERATION FOR THE MILLENNIAL GENERATION IN THE JENDRAL SUDIRMAN MOSQUE YOGYAKARTA - Abd. Aziz Faiz; M Mujibuddin (Balai Penelitian dan Pengembangan Agama Makassar, 2023)
The mosque is a religious institution with two functions: a place of worship and the formation of religious awareness (education). The role is also found in the Jendral Sudirman Mosque (MJS), which functions as a place of worship and for forming religious awareness. The construction of religious understanding at MJS is dynamic. In the 1980s, MJS was known as a place of indoctrination for Salafi-jihadi views, while in the 2010s, it was known as a cultural mosque. The change from an Islamic mosque to a cultural mosque underwent a long process. This study aims to analyze the role of agents in providing change while also forming an awareness of local culture-based religious moderation in the millennial generation. This study uses observation and interviews to find data. This study uses Pierre Bourdieu's theory of cultural reproduction to analyze an agent's role in shaping a mosque's identity. This research found three things: First, the transformation of the MJS from an Islamic mosque to a culture-moderate mosque occurred because of the accumulation of agent capital at stake in the mosque arena and formed a new habitual space. Second, MJS is a discursive space that leads to the dissemination of local culture-based religious moderation with contextualization patterns between Islam, culture, and modernity. Third, mosque-based moderation is disseminated using popular language styles and humour to make it easier for congregations to understand the material. This study concludes that the agent has an essential role in determining the identity of the mosque.